The Developing of Pedagogical Competence of Madrasah Ibtidaiyah Teachers Through Formative Assessment Management - Hikmah, Nur; Asikin, Ali; Syfa, Layinatul; Sabila, Aulia Firda (Universitas Islam Negeri Walisongo Semarang in collaboration with PD PGMI Indonesia, 2024)
Formative assessments play a crucial role in providing valuable feedback to both teachers and students, highlighting progress and pinpointing areas for improvement. This study focuses on the development of teacher competence through the planning, organization, implementation, and supervision of formative assessments at Elementary School. It is a descriptive and qualitative research employing interviews, documentation, and observation methods to gather data, ensuring data validity through triangulation techniques. Data analysis involves collection, presentation, and drawing conclusions. The findings indicate that teachers' pedagogical competence is enhanced through effective formative assessment management, evidenced by thoughtful planning, meticulous organization, and comprehensive execution of formative assessments. Responsibilities for supervision are distributed among Madrasah Heads and Madrasah Supervisors. The study's implications suggest that strengthening teacher supervision in formative assessments can lead to improved pedagogical practices, ultimately enhancing student learning outcomes.